Rules of Thumb for Bank Solvency Stress Testing - Hardy, Daniel (IMF Working Papers; Working Paper ;, 2013)
Rules of thumb can be useful in undertaking quick, robust, and readily interpretable bank stress tests. Such rules of thumb are proposed for the behavior of banks' capital ratios and key drivers thereof-primarily credit losses, income, credit growth, and risk weights-in advanced and emerging economies, under more or less severe stress conditions. The proposed rules imply disproportionate responses to large shocks, and can be used to quantify the cyclical behaviour of capital ratios under various regulatory approaches.